Constructive Thought for Teaching Entrepreneurship: Case of John Davison Rockefeller School Quito - Ecuador - Benalcázar-Atiencia, Nelson Iván (2019)
This study was carried out with the purpose of analyzing the development of constructive thinking and the teaching of entrepreneurship in middle education schools, taking as a case of study the John Davison Rockefeller College, located in the city of Quito. The sample were 45 students from the 4th, 5th and 6th courses, within the ages of 15 to 19 years old, who responded to the CTI questionnaire applied to this effect, allowing us to analyze the emotional development, physical health and certain values, like the liability aspects they are acquiring in their personal lives and their impact on the education methods in the students of secondary level in order to prepare creative and innovative entrepreneurial projects.